2009
DOI: 10.1111/j.1460-9568.2009.06666.x
|View full text |Cite
|
Sign up to set email alerts
|

Examination of intravenous and intra‐CSF protein delivery for treatment of neurological disease

Abstract: Mucopolysaccharidosis type IIIA is a neurodegenerative lysosomal storage disorder characterized by progressive loss of learned skills, sleep disturbance and behavioural problems. Absent or greatly reduced activity of sulphamidase, a lysosomal protein, results in intracellular accumulation of heparan sulphate. Subsequent neuroinflammation and neurodegeneration typify this and many other lysosomal storage disorders. We propose that intra-cerebrospinal fluid protein delivery represents a potential therapeutic ave… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
63
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
5
2
1

Relationship

4
4

Authors

Journals

citations
Cited by 63 publications
(66 citation statements)
references
References 35 publications
3
63
0
Order By: Relevance
“…These results were similar to those found in mature immunotolerized MPS-VI cats (14) and support the contention that repeated IT-INJ is a safe and efficacious means of regularly administering enzyme into the CNS in MPS-VI and other lysosomal storage disorders for which development of paresis needs to be prevented (6,7) or in which brain function is impaired (16,(23)(24)(25)28,29).…”
Section: Articlessupporting
confidence: 85%
See 1 more Smart Citation
“…These results were similar to those found in mature immunotolerized MPS-VI cats (14) and support the contention that repeated IT-INJ is a safe and efficacious means of regularly administering enzyme into the CNS in MPS-VI and other lysosomal storage disorders for which development of paresis needs to be prevented (6,7) or in which brain function is impaired (16,(23)(24)(25)28,29).…”
Section: Articlessupporting
confidence: 85%
“…MPS-I dogs treated intrathecally with recombinant human iduronidase developed serum and CSF antibodies against the enzyme, as well as meningitis (15,16). Similarly, intrathecally treated MPS-IIIA dogs developed antibodies against recombinant human sulfamidase, as well as meningitis (23), whereas MPS-IIIA mice treated with repeated IT-INJs of the same enzyme developed circulating antibodies without meningitis or adverse reactions (24)(25)(26). The small, focal, Wallerian-type degeneration observed near the site of IT-INJ in most intrathecally treated cats, irrespective of presence or absence of polysorbate-80, was attributed to mild iatrogenic trauma produced during IT-INJ, as previously reported (14), again highlighting the importance of a good injection technique (14).…”
Section: Articlesmentioning
confidence: 99%
“…The tissues were derivatized with 1-phenyl-3-methyl-5-pyrazolone (Sigma, MO, USA) and assessed by liquid chromatography electrospray ionization tandem mass spectrometry analysis using a PE Sciex API 4000 QTRAP triple quadrupole mass spectrometer with a turbo spray source, as previously described (Hemsley et al 2009). The intra-assay coefficient of variation of the quality control brain homogenate was 4.9%.…”
Section: Sgsh Activity and Glcns-ua Measurement In Tissue Homogenatesmentioning
confidence: 99%
“…In contrast, MPS IIIA mice (Bhaumik et al 1999;Bhattacharyya et al 2001;Crawley et al 2006) exhibit significant and early-disease-stage cognitive impairment, with deficits in open-field activity (exploration; Hemsley and Hopwood 2005;Lau et al 2008), elevated-plus maze activity (anxiety; Lau et al 2008), and performance of the Morris water maze test (memory and learning; Gliddon and Hopwood 2004;Fraldi et al 2007;Hemsley et al 2009b) reported. Motor changes are also observed, including gaitwidth abnormalities (Hemsley and Hopwood 2005;Crawley et al 2006) and swim speed (Hemsley et al unpublished data), albeit at later stages in the disease process.…”
Section: Do Animal Models Adequately Mimic Disease In Humans?mentioning
confidence: 99%